Correction: Glutamate dehydrogenase (Gdh2)-dependent alkalization is dispensable for escape from macrophages and virulence of Candida albicans. - Fitz Gerald S Silao (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.ppat.1008328.].